Agribusiness in South Asia - Chodavarapu, Soujanya (World Bank, Washington, DC, 2016)
Agribusiness (including agriculture) accounts for almost one third of South Asia’s GDP and has the potential to almost double over the next fifteen years (reaching 1.5 trillion US dollars by 2030). This increase will be driven by rapid growth in population, incomes and urbanization, as well as accelerated transformation of the sector towards higher value products and downstream activities. The highest growth will come from processed food and related services, such as food retail and restaurants which will create millions of productive jobs outside agriculture and positive backward linkages for farmers. Removing restrictions on trade, markets and prices would support this transformation; reforms in these areas are already showing promising effects. In addition, governments should continue to support smaller and poorer farmers, who may not benefit from this transformation. More targeted and pro-active support should be provided to raise productivity, rather than blanket subsidies and price controls that encourage the status quo and threaten the sustainability of the sector in the face of climate change (for example, large untargeted water subsidies).